CLASS IMPROVEMENT STRATEGIES FOR THE BINUANGEUN FISH LANDING BASE IN LEBAK REGENCY, BANTEN - Setiadi M Noor; Hafinuddin Hasaruddin; Muhammad Rizal; Zuriat Zuriat; Uswatun Hasanah; I Made Dwi Mertha Adnyana (Bogor Agricultural University, 2022)
The increase in fishing activities of fishers in the Lebak Regency is facilitated by the Binuangeun Fish Landing Base (PPI). Every year, there is a growth in fish production at PPI Binuangeun. Production from 2015 to 2019 increased by 671 tons (13.55%). This study aims at formulating and determining strategies for improving the PPI Binuangeun class category. A survey approach was used in this study. Samples were taken by purposive sampling. The improvement in PPI class were categorized using the Analytical Hierarchy Process (AHP) scoring method. Results showed that the score was 254 with a success value of 251-300, indicating high potential and standards fulfillment. Thus, PPI Binuangeun can be transferred and upgraded to PPP (Coastal Fishery Port). The results of the AHP suggested that the central priority values for the development of PPI Binuangeun include: supply, auction, landing and marketing activities with the priority value of 0.585. Subsequently, another strategy is expanding the port area with score of 0.409. The support of relevant stakeholders for the development of the fishing port is needed to realize the aspirations of the central and local governments. Keywords: Fishing activities, AHP, Fish Landing Base, Fish production.